Sialidase activity in Glioblastoma cells treated with thyme oil: Sialidase Role in Glioblastoma Cells - H Fadhil, ola; Hamad , Bushra Shihab; Abbas , Budoor Sattar; Abbas A. Mohammed (Iraqi Journal of Cancer and Medical Genetics, 2024)
Background: Cancer is a genetic disease that causes aberrant cells to grow and spread uncontrollably throughout the body, where cerebral glioblastoma is one of the brain tumors. Thyme oil has many therapeutic properties such as antioxidants and anticancer.Aim of study: Estimate sialidase enzyme in human glioblastoma cancer cell line (AMGM5) and rat embryo fibroblasts cell line (REF) in supernatant and suspension cells treated with thyme oil extract and cells without it. Methods: Sialidase activity was measured by ELISA (Enzyme-linked immunosorbent assay) in supernatant and suspension cells of AMGM5 and REF cells treated and untreated with thyme oil extract. Results: Sialidase showed a high level in the Glioblastoma cell line ( AMGM5), while a low level in cells after exposure to diluted thyme oil (10μl/ml) after incubation for 24 hours, also showed a lower level in the Rat Embryo Fibroblast after being treated with thyme extract.Conclusions The sialidase enzyme showed increased in glioblastoma cells but decreased in its level in these cells after exposure to thyme oil extract, which means that thyme oil inhibited cancer cell growth.